HUBUNGAN ANTAR USIA KEHAMILAN DENGAN JUMLAH LEUKOSIT PADA IBU HAMIL DI PUSKESMAS SLAHUNG PONOROGO - Suryani, Eka; Widhiyastuti, Endang (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Leukocytes are blood cells that play a role in the immune mechanism. Leukocytes are classified based on the presence or absence of granules in the cytoplasm of leukocytes, which consist of granulocytes and agranulocytes. The normal leukocyte count is 3200-10000/mm3 of blood. If the leukocytes are above the normal limit, it is called leukocytosis. Leukocytosis can be pathological or physiological. Physiological leukocytosis that occurs during pregnancy is common due to two reasons, namely a physiological stress and an increased inflammatory response. Physiological stress arises as a response to changes that occur in the body of pregnant women, including the workload of the heart, digestive system, metabolism, thereby stimulating the production of white blood cells to increase immunity. The inflammatory response is a form of the body's selective immune tolerance, immunosuppression and immunomodulation of the fetus. The purpose of this study was to determine the relationship between gestational age and leukocyte count in pregnant women at the Slahung Health Center, Ponorogo Regency, which was conducted in July 2021. This study uses an analytical observational analytic method with a cross sectional approach. This research was conducted by examining gestational age and leukocyte count in pregnant women with a total sample of 30 samples and using a total sampling technique. Examination of the number of leukocytes using the Hematology Analyzer URIT 3000 Plus. The results based on the average number of leukocytes from this study in the first trimester were 3.20 x103/mm3, in the second trimester 8.42 x103/mm3, and in the third trimester 12.56 x103/mm3. The results of test using the Kruskal-Walis obtained a significance value of 0.000 < 0.05. The results of this study can be concluded that there is a relationship between gestational age and the number of leukocytes in pregnant women